Evaluation of Coral Reef Transplantation Effectiveness on Coral Fish Populations and Communities in the Waters of Kapitu Village - Schaduw, Joshian Nicolas William; Wantasen, Adnan S.; Ngangi, Edwin L. A.; Pelle, Wilmy E.; Kusen, Janny D.; Tasidjawa, Sonny; Runtulalu, Sella; Oroh, Dannie. R.S.; Tandako, Imelda; Sorongan, Marthen (Jurnal Ilmiah PLATAX, 2025)
Coral reef fish are essential to the coral reef ecosystem as they forage, seek shelter, reproduce, and receive care. Experts use coral reef fish as indicators of habitat suitability, monitoring their populations and correlations to inform sustainable management. Coral transplantation in Kapitu Village, North Sulawesi, is expected to enhance fish populations and diversity, support marine ecosystems, and benefit local communities. Coral fish data collection in the transplantation area uses the Underwater Visual Census (UVC) method. Survey results indicate the relative abundance of coral fish families in the waters of Kapitu Village, with some families like Pomacanthidae and Acanthuridae showing significant abundance. A total of 12 families, 28 genera, and 39 species were documented in the UVC monitoring survey of the transplantation area, demonstrating the diversity of fish inhabiting the transplant sites. Keywords: Coral fish, coral transplantation, Kapitu Village waters. Abstrak Ikan karang merupakan bagian penting dari ekosistem terumbu karang karena mereka mencari makan, berlindung, memijah, dan asuhan di dalamnya. Para ahli menggunakan ikan karang sebagai indikator kesesuaian habitat, memantau populasi dan korelasinya untuk pengelolaan berkelanjutan. Transplantasi karang di Desa Kapitu Sulawesi Utara diharapkan dapat meningkatkan populasi dan keberagaman ikan, mendukung ekosistem laut, dan memberikan manfaat bagi masyarakat setempat. Pengambilan data ikan karang dilakukan di area transplantasi karang menggunakan Metode Underwater Visual sensus. Hasil survei menunjukkan kelimpahan relatif famili ikan karang di perairan Desa Kapitu, dengan beberapa famili seperti Pomacanthidae dan Acanthuridae memiliki kelimpahan signifikan. Terdapat 12 famili, 28 genus, dan 39 spesies yang terdokumentasi dalam survei monitoring ikan dengan metode UVC di area transplantasi perairan Desa Kapitu, hal ini menunjukkan adanya kenakeragaman ikan yang hidup pada daerah transplantasi. Kata Kunci: Ikan Karang, transplantasi karang, perairan Desa Kapitu